Child Marriage and Sexual Autonomy among Women in Sub-Saharan Africa: Evidence from 31 Demographic and Health Surveys - Budu, Eugene (Int J Environ Res Public Health, 2021)
Child marriage has a variety of undesirable consequences at the peril of women’s health and autonomy. In this study, we examined the association between child marriage and sexual autonomy among women in sub-Saharan Africa. We utilised data from the most recent Demographic and Health Surveys conducted in 31 countries in sub-Saharan Africa between 2010 and 2019. A total of 218,578 women aged 20–49 were included in this study. Multivariable binary logistic regression models were used to show the association between child marriage and sexual autonomy. Crude odds ratio (cOR) and adjusted odds ratio (aOR) were used in presenting the results. The prevalence of child marriage and sexual autonomy was 44.51% and 83.35%, respectively. Compared to women who married at 18 years or above, those who married at less than 18 were less likely to have sexual autonomy, and this persisted after controlling for important covariates. In terms of the country-specific results, women who experienced child marriage were less likely to have sexual autonomy in Burundi, Congo DR, Nigeria, and Niger. With the covariates, lower odds of sexual autonomy were found among women with no formal education, those whose partners had no formal education, those who were not exposed to media, and non-working women. Child marriage was found to be associated with sexual autonomy. There is a need to strengthen policies and programmes such as compulsory basic education, poverty alleviation, and an increase in access to media that aim at reducing child marriage. These interventions will help to improve sexual autonomy among women, especially in this 21st century where individuals and organisations incessantly advocate for gender equality.